2012
DOI: 10.1111/all.12012
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis in an emergency setting – elicitors, therapy and incidence of severe allergic reactions

Abstract: Our data show that food products are frequent elicitors of severe allergic reactions in the general population including children and adults. It unravels a strong underuse of adrenaline by emergency physicians, not reflecting treatment protocols according to the current guidelines. As data obtained from allergists reveal a different rank order of elicitors, this study suggests that food-allergic adult patients may present a risk population and should receive more attention by allergists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 35 publications
(52 reference statements)
10
61
0
17
Order By: Relevance
“…Orhan et al found that only 32.2% of their patients received epinephrine as treatment for anaphylaxis [17]. Beyer et al also found a low percentage of use of epinephrine in the ED in Berlin, where it was used in only 22.7% of cases [18]. Alvarez Perea et al, in an observational study of patients aged more than 15 years attended at the ED of a tertiary-level hospital in Spain, found that only 40% of patients received epinephrine, which was administered more frequently when the ED physician diagnosed anaphylaxis, regardless of severity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Orhan et al found that only 32.2% of their patients received epinephrine as treatment for anaphylaxis [17]. Beyer et al also found a low percentage of use of epinephrine in the ED in Berlin, where it was used in only 22.7% of cases [18]. Alvarez Perea et al, in an observational study of patients aged more than 15 years attended at the ED of a tertiary-level hospital in Spain, found that only 40% of patients received epinephrine, which was administered more frequently when the ED physician diagnosed anaphylaxis, regardless of severity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Food allergy, particularly to peanuts, tree nuts, egg, and milk, is the leading cause of anaphylaxis (7)(8)(9)(10). Allergen avoidance education is often targeted at avoidance within the home, with less emphasis on how to avoid community exposure.…”
Section: Why the Community Is Importantmentioning
confidence: 99%
“…Although the ratio of patients with anaphylaxis to all patients admitted to the ER was reportedly 0.08%,4 this ratio was likely to have been underestimated due to the difficulty in diagnosing anaphylaxis. In general, foods are the most common cause of anaphylaxis, although there is a wide variation in the ratio of food‐/non‐food‐induced anaphylaxis among studies 4, 6, 7, 8, 9. An important factor affecting the etiology of anaphylaxis is patient age 6, 10, 11, 12.…”
Section: Epidemiologymentioning
confidence: 99%
“…Concomitant symptoms of the skin and mucosal tissue, respiratory symptoms, and gastrointestinal symptoms were documented in 81.4%, 74.6%, and 31.5% of cases, respectively (Table 1). 8 The author pointed out that the symptoms in children and young adults are a little different from those in the elderly. For example, generalized pruritus and urticaria, vomiting, and diarrhea were more often reported in children and young adults 8.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation